Puisi “لا بد أن أستأذن الوطن” Karya Nizar Qubbani Dalam Bingkai Stilistika - Ashief El Qorny; Khasanah Khasanah; Rufaida Hindun Farhisiyati; Ahmad Rois (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2022)
This paper aims to examine the style of language used by Nizar Qubbani in his poetry with the theme of modern life by describing the main idea or theme, elements of feeling or emotion, and style of language based on aspects of diction or choice of words, syntax or sentence structure, and rhetorical aspects or meaning. . This article is a literature study which is analytically descriptive in nature by referring to the text of Nizar Qubbani's poetry as the primary source. The method of data analysis is content analysis with a stylistic approach to examining and analyzing the style of the poem's language. The stylistic theory put forward by Gorys Keraf will be used in understanding the types of diction, and language style based on syntactic aspects and rhetorical aspects or meaning. Poetry with the theme of